Modified Lengthening Temporalis Myoplasty Using an Intraoral Approach. Issue 3 (12th May 2022) - Hayashi, Ayato; Natori, Yuhei; Suda, Shunichi; Kamimori, Tomoki; Nojiri, Gaku; Uchiyama, Mizuki; Labbé, Daniel
Abstract : Background: Lengthening temporalis myoplasty (LTM) is a unique and definite facial reanimation procedure that involves inserting the whole temporal tendon directly into the nasolabial fold. However, the nasolabial fold incision remains one of the difficulties of this procedure, particularly in young or female patient. To avoid the need for this incision, the authors developed an intraoral approach to manipulate the temporal muscle tendon toward the nasolabial fold. in this study, we describe the details of this procedure. Method: The authors performed their intraoral approach procedure in 5 patients with established complete facial paralysis. instead of making an incision at the nasolabial fold to approach the coronoid process, the authors made the incision at the buccal mucosa. The results were evaluated both subjectively and objectively. Results: The authors achieved facial reanimation without leaving any obvious scar on the face or neck and the effect of static reconstruction is obvious, even immediately after the surgery. All the patients obtained good facial movement within 4 months (2.5 months in average), and improved all evaluated parameters postoperatively. No infections or other major complications were reported following surgery; however, 1 patient developed a slight dimple that required revision. Discussion: The authors could advance temporal tendon toward nasolabial fold firmly obtaining sufficient surgical field similar to that of nasolabial fold incision, and achieved fairly good results without an obvious scar on the face. Establishing LTM without nasolabial fold incision, we could expand the indication of LTM more widely, and it could be more familiar procedure for smile reanimation in all generation.